Penanganan Sign On Buku Pelaut Secara Online dan Manual pada KSOP Batam Oleh PT. Pelayaran Dwi Putra Laksana Batam - Rashida Mutia; Syarifur Ridho; Taruna Ginting (Jurnal Transformasi Bisnis Digital, 2025)
PT. Pelayaran Dwi Putra Laksana Batam operates in the sector of ship security services and shipping management (shipping agency), providing support for both domestic and international voyages. Its services include handling vessel arrival and departure permits, processing entry and exit permits for foreign crew members, renewing ship and crew certificates, and managing administrative procedures for seafarers’ sign-on and sign-off documentation. The document management process begins when crew members either sign a Sea Work Agreement (PKL) for employment on Indonesian-flagged ships or enter into a work agreement for service on foreign-flagged vessels. This paper employs field observation and literature review methods to present a comprehensive description of the document processing mechanisms at PT. Pelayaran Dwi Putra Laksana Batam based on operational requirements. The discussion focuses on outlining the workflow of seafarer book sign-on procedures, starting from the shipowner’s notification regarding scheduled crew changes to final administrative completion at the Batam Special KSOP Office. The sign-on document not only verifies the crew member’s official assignment but also functions as a record of their maritime service history. Common challenges include delays in information submission from shipowners, which can prevent timely sign-on and subsequently hinder vessel clearance. Therefore, strong coordination between shipping companies and regulatory agencies is essential to ensure effective fulfillment of responsibilities in managing crew documentation.